الخلاف النحوي في الفاعل الجملة: جمعاً ودراسة - الجهني، عبدالعزيز بن حميد بن محمد (جامعة قاصدي مرباح - ورقلة, 2017)
الحمد لله وحده والصلاة والسلام على من لا نبي بعده وبعد؛ فهذا بحث يتعلق بمسألة خلافية بين النحاة لم تأخذ حظها من الدرس في كتب الخلاف النحوي، وهي وقوع الفاعل جملة، وقد تتبعت في هذا البحث اختلاف النحاة البصريين والكوفيين في هذه القضية ، وأوردت أصحاب كل قول بتسلسل تاريخي، وأقوالهم فيها ثلاثة مشهورة، وقد سردت حجج كل قول وما جاء على هذه الحجج من إيرادات، مع العناية بتحقيق موقف بعض العلماء الذين نسب لهم أكثر من قول في هذه المسألة، وأردفت ذلك بخاتمة ذكرت فيها أهم نتائج البحث وفهرس للمصادر والمراجع وأخر للموضوعات.
This paper discusses the dispute among Arabic grammarians in regard to whether the doer of the action (agent) in a sentence can be a whole sentence. This dispute was among the least studied topics in the literature of Arabic grammar. The disagreement between the scholars of the two famous schools in Arabic grammar, Basra and Kufa, over this issue was historically traced and presented. Historically, there are three famous views and explanations. All of these were discussed in this paper. Moreover, the paper discussed the views of the scholar whom had more than one opinions in this debate. Finally, the paper concluded with the result of this discussion
Keywords: النحو العربي -- الخلاف النحوي -- الفاعل الجملة